2014
DOI: 10.1021/ie500928m
|View full text |Cite
|
Sign up to set email alerts
|

Ca0.9Mn0.5Ti0.5O3−δ: A Suitable Oxygen Carrier Material for Fixed-Bed Chemical Looping Combustion under Syngas Conditions

Abstract: Power generation using chemical looping combustion (CLC) technology has emerged as a promising CO 2 -capture-based alternative to conventional technology. In this study, the performance of a Ca 0.9 Mn 0.5 Ti 0.5 O 3−δ perovskite-type oxygen carrier material for use in fixed-bed CLC reactors is investigated. The main focus of the study is on the material's oxygencarrying capacity and reactivity with and conversion of syngas in the fixed-bed reactor. Pressurized thermogravimetric analysis in model gases indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Up to 8.8% decrease in initial decomposition temperature was reported for perovskite supported mixed metal oxides. As a standalone oxygen carrier, perovskites of the CaMnO 3 family are extensively studied for CLOU and CLC applications [20,[29][30][31][32][33][34][35][36][37][38][39]49,[57][58][59][60][61]. While its oxygen uncoupling capacity is smaller than copper oxides, CaMnO 3 , which can be synthesized from abundantly available manganese ores and Ca precursors [29,60], has been reported to be active for solid fuel conversions [29,31,34,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 8.8% decrease in initial decomposition temperature was reported for perovskite supported mixed metal oxides. As a standalone oxygen carrier, perovskites of the CaMnO 3 family are extensively studied for CLOU and CLC applications [20,[29][30][31][32][33][34][35][36][37][38][39]49,[57][58][59][60][61]. While its oxygen uncoupling capacity is smaller than copper oxides, CaMnO 3 , which can be synthesized from abundantly available manganese ores and Ca precursors [29,60], has been reported to be active for solid fuel conversions [29,31,34,36].…”
Section: Introductionmentioning
confidence: 99%
“…Pishahang et al investigated Ca 1Ày Mn 1Àx Ti x O 3Àd oxygen carriers under fixed bed conditions using syngas as the fuel [38]. The authors reported that adding Ti and decreasing the Ca content increased stability of the oxygen carrier.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, too‐early release of oxygen in the loop‐seal (the chamber filled with steam separating the air and fuel reactors) should be limited, and oxygen should be released as quickly as possible in the fuel reactor of a circulating fluidized bed (CFB) CLC system. This aspect is even more critical in the case of a fixed‐bed CLC reactor, in which oxygen release during inert flushing should be prevented . In addition to kinetics, the OCM must retain several qualities during the reduction/oxidation (redox) cycles such as high oxygen capacity, high redox kinetics, and good mechanical properties such as low fragmentation, low attrition, and low agglomeration.…”
Section: Introductionmentioning
confidence: 99%
“…For CLC applications, substitution of calcium by strontium and barium has been considered. Furthermore, the substitution of manganese by magnesium, titanium, or a combination of both has been investigated. Substantial improvements from iron substitution were reported .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, for gas‐based CLC, sophisticated OCMs with longer lifetimes are of greater interest. OCMs with perovskite‐type structures are attracting increasing interest thanks to their redox tunability by controlling various dopants in the structure . Perovskites are normally formulated as ABO 3− δ , in which A is a large alkaline earth or rare earth and B is a smaller transition‐metal cation .…”
Section: Introductionmentioning
confidence: 99%